Reputation management of ukrainian political opinion leaders on social media in times of war (the Serhiy Prytula case) - Goroshko, Olena; Kashhyrova, Nataliia (Jagiellonian University in Kraków, 2024)
The main objective of this study is to ask how the reputation of personalities on social media is established during times of war, what its components are, and what factors influence it during the rapidly changing context of wartime. Among the factors that influence public image, one can speak about the values and cultural characteristics of the target audience, the duration of reputation, social cohesion and solidarity with active groups in society to fight against the aggressor, co-experiencing the trauma caused by war, and co-writing a history stored in the collective memory of the people, the lexical colouring of the text used, and orientation towards traditional values. The case selected for the study is Serhiy Prytula, a famous Ukrainian media person, public activist and founder of the Serhiy Prytula Charity Foundation. Serhiy Prytula’s posts on social platforms (Telegram, Facebook, and Instagram) in the period of Ukraine’s announced counter-offensive in June 2023 were chosen for the research. Employing a methodology based on thematic and content analysis of social media posts, the authors identify the components and factors influencing reputation. The picture of the Ukrainian society in wartime built by opinion leaders across social networks shows a changing society, where volunteering is a positive trend but resentment is an alarming tendency – the desire to take revenge and blame other people for one’s problems, which contributes to justifying Russia’s military aggression.
Keywords: online reputation; opinion leader; social media; war; Ukraine